Use the graph to find (gof)(-4)
![Use the graph to find gof4 class=](https://us-static.z-dn.net/files/d4e/e074d6d31e250e0826cf97138e91f646.png)
Explanation:
The notation (g o f)(-4) is the same as saying g( f(-4) ). Note the order of g and f are kept the same between the notation styles.
The inner function f(-4) is computed first. We then work our way outward.
The graph f(x) shows that plugging x = -4 leads to y = 0.
Because f(-4) = 0, this indicates g( f(-4) ) becomes g( 0 )
We then repeat this process of using the graph but this time for the g(x) function. We see that g(0) = 2.
Therefore, g( f(-4) ) = 2